Peptide YY (PYY) is associated with cardiovascular risk in patients with acute myocardial infarction - Haj-Yehia, Elias; Mertens, Robert Werner; Kahles, Florian; Rückbeil, Marcia Viviane; Rau, Matthias; Moellmann, Julia; Biener, Moritz; Almalla, Mohammad; Schroeder, Jörg; Giannitsis, Evangelos; Katus, Hugo; Marx, Nikolaus; et al. (Journal of Clinical Medicine, 2020)
Aims: Recent studies have found circulating concentrations of the gastrointestinal hormone GLP-1 to be an excellent predictor of cardiovascular risk in patients with myocardial infarction. This illustrates a yet not appreciated crosstalk between the gastrointestinal and cardiovascular systems, which requires further investigation. The gut-derived hormone Peptide YY (PYY) is secreted from the same intestinal L-cells as GLP-1. Relevance of PYY in the context of cardiovascular disease has not been explored. In this study, we aimed to investigate PYY serum concentrations in patients with acute myocardial infarction and to evaluate their association with cardiovascular events. Material and Methods: PYY levels were assessed in 834 patients presenting with acute myocardial infarction (553 Non-ST-Elevation Myocardial Infarction (NSTEMI) and 281 ST-Elevation Myocardial Infarction (STEMI)) at the time of hospital admission. The composite outcomes of first occurrence of cardiovascular death, nonfatal myocardial infarction, nonfatal stroke (3-P-MACE), and all-cause mortality were assessed with a median follow-up of 338 days. Results: PYY levels were significantly associated with age and cardiovascular risk factors, including hypertension, diabetes, and kidney function in addition to biomarkers of heart failure (NT-pro BNP) and inflammation (hs-CRP). Further, PYY was significantly associated with 3-P-MACE (HR: 1.7; 95% CI: 1-2.97; p = 0.0495) and all-cause mortality (HR: 2.69; 95% CI: 1.61-4.47; p = 0.0001) by univariable Cox regression analyses, which was however lost after adjusting for multiple confounders. Conclusions: PYY levels are associated with parameters of cardiovascular risk as well as cardiovascular events and mortality in patients presenting with acute myocardial infarction. However, this significant association is lost after adjustment for further confounders.
Gesehen am 17.02.2022